#1**0 **

One question per post! I will solve No. 9

Solve for x:

x^3 - 4 x^2 + x + 26 = 0

The left hand side factors into a product with two terms:

(x + 2) (x^2 - 6 x + 13) = 0

Split into two equations:

x + 2 = 0 or x^2 - 6 x + 13 = 0

Subtract 2 from both sides:

x = -2 or x^2 - 6 x + 13 = 0

Subtract 13 from both sides:

x = -2 or x^2 - 6 x = -13

Add 9 to both sides:

x = -2 or x^2 - 6 x + 9 = -4

Write the left hand side as a square:

x = -2 or (x - 3)^2 = -4

Take the square root of both sides:

x = -2 or x - 3 = 2 i or x - 3 = -2 i

Add 3 to both sides:

x = -2 or x = 3 + 2 i or x - 3 = -2 i

Add 3 to both sides:

**x = -2 or x = 3 + 2 i or x = 3 - 2 i**

Guest Oct 2, 2020